THE FINANCIAL CRISES, INCOME LEVELS AND THE DEPTH OF THE FINANCIAL SYSTEM - HALIL D. KAYA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
In this study, we investigate whether the depth of the financial markets around the world was significantly impacted by the 2008-2009 global crisis. We examine 11 variables on depth. First, we run tests to see if there was a significant change in any of the variables during the run-up to the crisis (i.e. 2006-2007). We find that, during the run up period, the high-income countries were not significantly impacted by the crisis in terms of market depth. On the other hand, a few of the variables significantly changed for the middle-income and low-income countries. For the middle-income countries, both stock market capitalization and the total stock value traded had significantly increased during this period. For the low-income countries, the total stock value traded had significantly increased. Then, we examine the crisis period (i.e. 2007-2008). We find that, during this period, only high-income OECD countries are significantly affected in terms of depth of the market. Stock market capitalization, gross portfolio equity liabilities, and gross portfolio equity assets went down significantly for this group during the crisis period. We do not find any significant change in any of the depth measures for the high-income non-OECD, the middle-income, and the low income groups during the crisis period. Finally, we examine the post-crisis period (i.e. 2008-2009 period). During this period, again only high-income OECD countries are affected in terms of depth of the market (except for one variable for the middle-income group). During the post-crisis period, for the high-income OECD group, stock market capitalization continued to go down significantly. The total stock value traded also went down significantly. Gross portfolio equity liabilities and assets recovered (i.e. increased) and gross portfolio debt liabilities also increased during the post-crisis period. Overall, we conclude that the middle- and low-income groups were affected during the run-up period (i.e. mostly positive; trading volumes increased for both groups and stock market capitalization increased for the middle-income group) and the high-income OECD group was affected during both the crisis and the post-crisis period (mostly negative). We conclude that the global crisis had a negative impact on the depth of the markets in the more developed countries only. Policymakers in the developed nations may benefit from these findings by focusing on the areas that are more vulnerable to a global economic/financial crisis. The stock market values and the trading volume seem to be the main problems in terms of depth of the market when these countries face such a crisis.